The Effect of Transfer Pricing and Firm Size on Financial Performance with Liquidity as a Moderating Variable in Manufacturing Companies Listed on The Indonesia Stock Exchange (IDX) - Hanif AR, Muh Amir; Usman, Asri; Alimuddin, Alimuddin (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
Manufacturing companies listed on the Indonesia Stock Exchange (IDX) face challenges in improving financial performance amidst global competition. Transfer pricing is used to optimize profits, while firm size is believed to affect operational stability. This study aims to examine the impact of transfer pricing and firm size on financial performance, with liquidity as a moderating variable. The research utilizes secondary data from financial statements for the 2021-2023 peri-od. The analysis method employed is Moderated Regression Analysis (MRA) to evaluate direct effects and the interaction of the moderating variable. The results show that transfer pricing has a positive and significant impact on financial performance, while firm size does not significantly influence it. Additionally, liquidity does not moderate the relationship between independent var-iables and financial performance. This study highlights the importance of transfer pricing as a fi-nancial efficiency strategy without reliance on liquidity as a moderating factor.